2020
DOI: 10.2147/rmhp.s252270
|View full text |Cite
|
Sign up to set email alerts
|

<p>Role of Global Self-Esteem, Professional Burnout and Selected Socio-Demographic Variables in the Prediction of Polish Nurses’ Quality of Life – A Cross-Sectional Study</p>

Abstract: The aim of the study was to analyze the role of global self-esteem and professional burnout in predicting Polish nurses' quality of life. Materials and Methods: The research involved 1806 nurses who were employed in 23 hospitals in north-eastern Poland. Forty-seven percent of nurses, aged ≤44 years, were qualified to Group 1, while 53% of nurses, aged ≥45 years, were included in Group 2. A diagnostic survey was applied as a research method. For the collection of data, the WHOQoL-Bref questionnaire, the Rosenbe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 50 publications
0
19
0
1
Order By: Relevance
“…The negative relationship between self‐esteem and psychological distress has been confirmed in various groups, including patients, pregnant women, and university students 23‐25 . Studies have shown that nurses with high self‐esteem cope better with burnout and are less likely to engage in absenteeism than those with low self‐esteem 26 . In Li et al's study, 27 which investigated the relationship between burnout and self‐esteem among Chinese nurses, nurses with higher self‐esteem reported a lower level of emotional breakdown and a higher level of business success than did those with lower self‐esteem.…”
Section: Discussionmentioning
confidence: 97%
“…The negative relationship between self‐esteem and psychological distress has been confirmed in various groups, including patients, pregnant women, and university students 23‐25 . Studies have shown that nurses with high self‐esteem cope better with burnout and are less likely to engage in absenteeism than those with low self‐esteem 26 . In Li et al's study, 27 which investigated the relationship between burnout and self‐esteem among Chinese nurses, nurses with higher self‐esteem reported a lower level of emotional breakdown and a higher level of business success than did those with lower self‐esteem.…”
Section: Discussionmentioning
confidence: 97%
“…Most of the included studies have explicitly concluded that nurses' BO or its' subscales negatively impacts their QOL or its' subscales (Abraham & D'silva, 2013;Alotni & Elgazzar, 2020;Aytekin et al, 2013;Fradelos et al, 2014;Hatamipour et al, 2017;Kelleci et al, 2011;Khatatbeh et al, 2020;Kupcewicz & Jóźwik, 2020;Ribeiro et al, 2021;Zeng et al, 2020). Similarly, some of the included studies found a negative association between professional or work-related QOL and nurses' BO (Abdel-Aziz & Adam, 2020;Casida et al, 2019;Erkorkmaz et al, 2018;Kim et al, 2019;Permarupan et al, 2020;Wang et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Most of the studies ( n = 12) included were from China, Turkey, Iran, Greece or Pakistan (Aytekin et al., 2013; Azari & Rasouyar, 2016; Çelmeçe & Menekay, 2020; Erkorkmaz et al., 2018; Fradelos et al., 2014; Hatamipour et al., 2017; Kelleci et al., 2011; Naz et al., 2016; Paniora et al., 2017; Wang et al., 2019; Wu et al., 2011; Zeng et al., 2020). The rest of the studies was from Brazil (Ribeiro et al., 2021), Egypt (Abdel‐Aziz & Adam, 2020), Korea (Kim et al., 2019), India (Abraham & D’silva, 2013), Jordan (Khatatbeh et al., 2020), Malaysia (Permarupan et al., 2020), Poland (Kupcewicz & Jóźwik, 2020), Saudi Arabia (Alotni & Elgazzar, 2020) and the USA (Casida et al., 2019). All of the studies included in this systematic review utilized a cross‐sectional design, and most of them ( n = 11) were published between 2019 and 2021, Table 1.…”
Section: Methodsmentioning
confidence: 99%
“…Tal achado discorda de estudo prévio realizado com 1.806 enfermeiros na Polônia, que encontrou relação entre idade e qualidade de vida, com a observação de maior qualidade de vida nos enfermeiros mais jovens em relação aos mais velhos. (26) Observa-se que parte dos enfermeiros participantes trabalha em hospitais, o que pode impactar negativamente na saúde física e mental dos profissionais, sendo que o baixo nível de AF entre os profissionais de saúde está fortemente relacionado à fatores de impacto negativo na qualidade de vida. (27) Um estudo realizado em um hospital universitário nos EUA com diferentes profissionais, encontrou que os enfermeiros possuem um nível satisfatório de AF durante a jornada de trabalho, sugerindo que a intensidade física das tarefas do hospital é alta.…”
Section: Discussionunclassified